The Effect of Open Umemployment Rate and Expected Years of Schooling on the Poor Population In East Java Province - Nathasya, Putri; M. Afdal Samsuddin; Rowiyah Asengbaramae (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2025)
Poverty in East Java Province remains a serious challenge despite various development efforts. This study aims to analyze the effect of open unemployment rate and expected years of schooling on the number of poor people in 38 districts/cities in East Java during the 2019-2023 period. The method used is panel data analysis with the Fixed Effect Model (FEM) approach, using secondary data from the Central Bureau of Statistics. The results showed that the open unemployment rate has a positive and significant effect on the number of poor people, meaning that an increase in unemployment will increase the number of poor people. In contrast, expected years of schooling has a negative and significant effect, meaning that the higher the expected years of schooling, the lower the number of poor people. This finding confirms the importance of government intervention in creating jobs and improving the quality of education as a strategy to alleviate poverty in East Java. This research is expected to serve as a reference for more effective and sustainable policy making in an effort to reduce poverty in this region.